Racial and Sex Disparities in Trauma Outcomes Based on Geographical Region. Issue 6 (June 2021) - Duong, William Q.; Grigorian, Areg; Farzaneh, Cyrus; Nahmias, Jeffry; Chin, Theresa; Schubl, Sebastian; Dolich, Matthew; Lekawa, Michael
Objectives: Disparities in outcomes among trauma patients have been shown to be associated with race and sex. The purpose of this study was to analyze racial and sex mortality disparities in different regions of the United States, hypothesizing that the risk of mortality among black and Asian trauma patients, compared to white trauma patients, will be similar within all regions in the United States. Methods: The Trauma Quality Improvement Program (2010-2016) was queried for adult trauma patients, separating by U.S. Census regions. Multivariable logistic regression analyses were performed for each region, controlling for known predictors of morbidity and mortality in trauma. Results: Most trauma patients were treated in the South (n = 522 388, 40.7%). After risk adjustment, black trauma patients had a higher associated risk of death in all regions, except the Northeast, compared to white trauma patients. The highest associated risk of death for blacks (vs. whites) was in the Midwest (odds ratio [OR] 1.30, P < .001). Asian trauma patients only had a higher associated risk of death in the West (OR 1.39, P < .001). Male trauma patients, compared to women, had an increased associated risk of mortality in all four regions. Discussion: This study found major differences in outcomes among different races within different regions of the United States. There was also both an increased rate and associated risk of mortality for male patients in all regions. Future prospective studies are needed to identify what regional differences in trauma systems including population density, transport times, hospital access, and other trauma resources explain these findings.